2018
DOI: 10.1001/jamapediatrics.2017.3913
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neonatal Intensive Care Unit Admission Rates and Illness Acuity

Abstract: IMPORTANCE Most neonates admitted to a neonatal intensive care unit (NICU) are born at gestational age (GA) of 34 weeks or more. The degree of uniformity of admission criteria for these infants is unclear, particularly at the low-acuity end of the range of conditions warranting admission.OBJECTIVES To describe variation in NICU admission rates for neonates born at GA of 34 weeks or more and examine whether such variation is associated with high illness acuity or designated facility level of care. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 20 publications
3
70
0
Order By: Relevance
“…However, the numbers of intermediate NICU admissions, patient-days, and antibiotic-days did not significantly differ across years, nor were EOS rates higher than at other levels of NICUs (Table 2). Therefore, antibiotic overuse is clearest at intermediate NICUs with both a relatively high AUR and inborn admission rate, and this may support other observations 23 , 24 that reveal a component of supply-sensitive care 25 , 26 . Supply-sensitive care has little evidence base, reflecting instead available service capacity and payment systems that are used to incentivize resource use.…”
Section: Discussionsupporting
confidence: 75%
“…However, the numbers of intermediate NICU admissions, patient-days, and antibiotic-days did not significantly differ across years, nor were EOS rates higher than at other levels of NICUs (Table 2). Therefore, antibiotic overuse is clearest at intermediate NICUs with both a relatively high AUR and inborn admission rate, and this may support other observations 23 , 24 that reveal a component of supply-sensitive care 25 , 26 . Supply-sensitive care has little evidence base, reflecting instead available service capacity and payment systems that are used to incentivize resource use.…”
Section: Discussionsupporting
confidence: 75%
“…In our cohort, 74% of the infants admitted were ≥34 weeks' gestational age, similar to the 80% reported in California. 10 Fifteen percent of infants ≥34 weeks' gestational age were high acuity, similar to 12% in California. 10 Ten percent of infants in our cohort stayed no more than 3 days and were discharged from the hospital.…”
Section: Discussionmentioning
confidence: 89%
“…22 Fifteen percent of infants ≥34 weeks' gestational age were high acuity. Our definition of high acuity, which was modeled after Schulman et al, 10 does not include all types of acute issues that may require NICU admission. Ziegler et al 11 identified 16 reasons, ranging from infection to brain injury to respiratory issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations